Technology Education for Teachers
VI, 264 p.
Keywords: This is a textbook for use in technology teacher training and also a reference book for technology teachers. It will provide a foundation for new teachers entering the area of technology, and also the opportunity for practicing teachers to keep up to date with research informed ideas about teaching technology. Technology in the curriculum has continually faced a range of challenges throughout its history in many counties. Often the basis of the challenges is the result of a lack of understanding about good technology practice. It is hoped that this book can encourage excellent practice in technology teaching and so increase the number of schools positively engaged with technology. The chapter authors are internationally respected and experienced educators who have been able to draw on both their teaching experience and their research in order to discuss a range of aspects of teaching technology. The book has been developed with an international audience in mind. While authors are naturally most familiar with their own country, efforts have been made to generalize from the principles of sound theory and research based practice to maximize applicability to local contexts. John Williams is the Director of the Technology, Environmental, Mathematics and Science Education Research Centre at the University of Waikato in New Zealand. He has worked as a designer and builder, and began his career as a secondary school Manual Arts teacher. He has taught and studied in Australia and the USA, and in a number of African and Indian Ocean countries. He has published and presented widely, and enjoys fishing.